PENATALAKSANAAN HOLISTIK WANITA USIA 50 TAHUN DENGAN NEURODERMATITIS MELALUI PRINSIP PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS SUMUR BATU - Nurladira, Salsanisa Tisno; Utama, Winda Trijayanthi (Medula, 2024)
Neurodermatitis Circumscripta is a chronic inflammatory skin condition that often occurs in individuals aged 30 - 50 years, characterized by itching and thickening of the skin due to repeated friction. Applying the principles of family medicine and implementing holistic management based on the patient-centered, family-focused, and community oriented approach grounded in Evidence-Based Medicine. This study is a case report utilizing primary data obtained through anamnesis, physical examination, and home visits to get family, psychosocial, and enviromental data. Secondary data were obtained from the patient’s medical records. Patient Mrs. I, 50 years old, came with a complaint of itching on the back of the right leg since the last 3 months, the itching increased when the patient was resting or at night. The patient often scratched it, causing thickening and darkening of the skin. The patient was diagnosed with neurodermatitis circumscripta. Holistic management was performed with a family physician-designed approach for Mrs I, 50 years old, with neurodermatitis based on the initial holistic diagnosis. The intervention has improved the patient’s knowledge and changed some behaviours of the patient and her family.